Suwung Landfill Closure as Acceleration to Improve Bali Waste Management System - Ida Bagus Komang Surya Werdiyasa (Bali Tourism Board, 2023)
The Suwung landfill, located in Suwung Kauh Village, Denpasar City, has been gradually terminated since November 2022. Official closure began in March 2023 by the Bali Provincial Forestry and Environment Service and continued with the operation of three new integrated waste management sites in Denpasar City. Governor Koster argued that the previous policy related to the Suwung landfill was tactless. Its placement in Denpasar city discouraged the strategic area in Bali as well as the capital city of Bali. The growth of Bali's economy by 61% in 2019 was mostly due to the expansion of hotels, restaurants, and other tourism-related enterprises. It led to a rising figure of visitors, a movement of laborers, and increased population density on the island's business corridors. In contrast, Bali's dense population harms the ecosystem, essential to the island's reputation as a tourist destination. According to recent conversations, the trash management system will be accommodated at three Integrated Waste Treatment Sites (TPST) in Denpasar City beginning in June 2023. The TPS3R will no longer be built with the TPST, which is expected to be fully operational in June 2023.